An exploratory analysis of citizen journalists as editorial gatewatchers - Maritha Pritchard; Charmaine du Plessis (Communicare)
This study is a qualitative analysis of citizen journalists’ blog posts relating to the Gautrain Project in South Africa, with a main focus on the Gautrain’s readiness to commence operations on 8 June 2010 for the 2010 FIFA Soccer World Cup. This article is based on sections of a current MTech study on citizen journalism. Citizen journalism as a phenomenon is examined within the context of the blogosphere. The gatekeeping theory is used as an approach to journalism in the online environment. So far, only a very limited number of studies have specifically addressed gatekeeping in the online environment where citizen journalists decide what is news and which issues need to be raised on the public sphere agenda. In the online context this is sometimes referred to as gatewatching. Although not professionally trained journalists, citizen journalists often perform the same gatekeeping functions as professional journalists. As gatewatchers of mainstream media content, press releases and other background information, citizen journalists may reintroduce debate in the public sphere and introduce new insights previously overlooked by the mainstream media. This article demonstrates how citizen journalists acted as editorial ‘gatewatchers’ on the topic of the Gautrain project’s readiness for the 2010 FIFA Soccer World Cup in terms of seven categories. It also illustrates that when functioning as editorial gatewatchers, citizen journalists have the potential to establish new criteria for newsworthiness in the public sphere.